2020
DOI: 10.1074/jbc.ra120.014883
|View full text |Cite
|
Sign up to set email alerts
|

Nitro-fatty acids as activators of hSIRT6 deacetylase activity

Abstract: Sirtuin 6, SIRT6, is critical for both glucose and lipid homeostasis and is involved in maintaining genomic stability under conditions of oxidative DNA damage such as those observed in age-related diseases. There is an intense search for modulators of SIRT6 activity, however, not many specific activators have been reported. Long acyl-chain fatty acids have been shown to increase the weak in vitro deacetylase activity of SIRT6 but this effect is modest at best. Herein we report that electrophilic nitro-fatty ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 85 publications
(109 reference statements)
0
11
0
Order By: Relevance
“…Interestingly, the SIRT6 catalytic pocket accommodates long-chain fatty acids, which stimulate the deacetylase activity (14). More recently, we have shown that long chain nitro-fatty acids potentiate SIRT6 deacetylase activity even in the presence of long chain fatty acids (15), suggesting that fatty acids are important players in the regulation of SIRT6. Notably, recent findings show that in cultured macrophages and mouse embryonic fibroblasts (MEFs), SIRT6 efficiently removes fatty acid groups from proteins.…”
Section: Introductionmentioning
confidence: 95%
“…Interestingly, the SIRT6 catalytic pocket accommodates long-chain fatty acids, which stimulate the deacetylase activity (14). More recently, we have shown that long chain nitro-fatty acids potentiate SIRT6 deacetylase activity even in the presence of long chain fatty acids (15), suggesting that fatty acids are important players in the regulation of SIRT6. Notably, recent findings show that in cultured macrophages and mouse embryonic fibroblasts (MEFs), SIRT6 efficiently removes fatty acid groups from proteins.…”
Section: Introductionmentioning
confidence: 95%
“…Thus, native fatty acids have no impact on cell and tissue inflammatory responses at the nM to low μM concentration ranges where small molecule electrophiles induce signaling responses and no toxicity. Notably, even the 10-nitro derivative of octadecanoic (stearic) acid, a nitroalkane lacking the crucial 9,10 double bond of 10-nitro-octadec-9-enoic acid, displays none of the signaling activities or cell/tissue responses induced by the nitroalkene NO 2 -OA [ 32 , 68 , [72] , [73] , [74] , [75] ]. Preliminary studies in the present PCLS model of fibrosis revealed no native oleic acid effects.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, LA was used at physiological concentrations to induce a conformational change that activated SIRT6 acetylation activity, which was not observed with other sirtuins 12 . A recent study revealed that nitrated fatty acids with a Michael adduct resulted in 20-fold stronger activation of SIRT6 39 . An unexpected finding was that the SIRT6 protein level was elevated by LA treatment in our model.…”
Section: Discussionmentioning
confidence: 99%